2018
DOI: 10.1016/j.celrep.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Prion-like Propagation of α-Synuclein Is Regulated by the FcγRIIB-SHP-1/2 Signaling Pathway in Neurons

Abstract: Recent evidence of prion-like propagation of α-synuclein (α-syn) into neighboring neurons set up a paradigm to elucidate the mechanism of progression of Parkinson's disease (PD) and to develop therapeutic strategies. Here, we show that FcγRIIB expressed in neurons functions as a receptor for α-syn fibrils and mediates cell-to-cell transmission of α-syn. SHP-1 and 2 are activated downstream by α-syn fibrils through FcγRIIB and play an important role in cell-to-cell transmission of α-syn. Also, taking advantage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 49 publications
2
89
0
Order By: Relevance
“…For example, interaction of aggregated a‐syn with FcγRIIB (an inhibitory FcγR) in neurons via endocytosis leads to the phosphorylation of the FcγRIIB immunoreceptor tyrosine‐based inhibitory motif. This phosphorylation through a downstream mechanism involving SH‐containing tyrosine phosphatase 1/2, (SHP 1/2), resulted in enhancement of a‐syn uptake (Choi et al., ). One study reported that the immune receptor lymphocyte activation gene 3 (LAG3) (Mao et al., ) is necessary to mediate the uptake of a‐syn in neurons, although expression of LAG3 in neurons has not been confirmed by other studies and LAG3 may be more relevant for the uptake of a‐syn by immune cells.…”
Section: The Role Of A‐synuclein In the Microglia Response In Parkinsmentioning
confidence: 99%
“…For example, interaction of aggregated a‐syn with FcγRIIB (an inhibitory FcγR) in neurons via endocytosis leads to the phosphorylation of the FcγRIIB immunoreceptor tyrosine‐based inhibitory motif. This phosphorylation through a downstream mechanism involving SH‐containing tyrosine phosphatase 1/2, (SHP 1/2), resulted in enhancement of a‐syn uptake (Choi et al., ). One study reported that the immune receptor lymphocyte activation gene 3 (LAG3) (Mao et al., ) is necessary to mediate the uptake of a‐syn in neurons, although expression of LAG3 in neurons has not been confirmed by other studies and LAG3 may be more relevant for the uptake of a‐syn by immune cells.…”
Section: The Role Of A‐synuclein In the Microglia Response In Parkinsmentioning
confidence: 99%
“…There is a bulk of information regarding prion-like propagation of neuronal α-synuclein in several in vivo and vitro paradigms of LBDs (Ulusoy et al, 2015;Rey et al, 2016;Shimozawa et al, 2017;Choi et al, 2018; just to include additional references to those signaled in previous paragraphs).…”
Section: Lewy Body Diseasesmentioning
confidence: 99%
“…The spread of α‐synuclein aggregation during the course of the disease is suggestive of prion‐like transmission of pathogenic α‐synuclein species, for which there is now extensive evidence . Several animal models based on the concept of injecting preformed α‐synuclein fibril fragments (PFFs) into the brain or peripherally have reinforced the concept of prion‐like transmission and revealed potential receptors such as lymphocyte‐activation gene 3 and FcγRIIB . Exogenous application of PFFs in mice caused aggregation of endogenous α‐synuclein followed by dopamine neuron demise .…”
Section: α‐Synuclein a Key Contributor To Pd Pathologymentioning
confidence: 99%
“…111 Several animal models based on the concept of injecting preformed α-synuclein fibril fragments (PFFs) into the brain or peripherally have reinforced the concept of prion-like transmission [112][113][114][115][116][117] and revealed potential receptors such as lymphocyteactivation gene 3 118 and FcγRIIB. 119 Exogenous application of PFFs in mice caused aggregation of endogenous α-synuclein followed by dopamine neuron demise. 112 Moreover, time-resolved imaging of α-synuclein inclusion-bearing neurons and neighboring neurons without inclusions indicated a selective degeneration of inclusion-bearing cells, providing evidence that α-synuclein aggregation causes neurodegeneration.…”
Section: α-Synuclein Aggregation In Diseasementioning
confidence: 99%